Archaeometallurgy in global perspective : methods and syntheses - Thornton, Christopher P.; Roberts, Benjamin W. (Springer New York, 2014)
The study of ancient metals in their social and cultural contexts has been a topic of considerable interest in archaeology and ancient history for decades, partly due to the modern dependence on technology and man-made materials. The formal study of Archaeometallurgy began in the 1970s-1980s, and has seen a recent growth in techniques, data, and theoretical movements.  This comprehensive sourcebook on Archaeometallurgy provides an overview of earlier research as well as a review of modern techniques, written in an approachable way. Covering an extensive range of archaeological time-periods and regions, this volume will be a valuable resource for those studying archaeology worldwide. It provides a clear, straightforward look at the available methodologies, including:  •• Smelting processes •• Slag analysis •• Technical Ceramics •• Archaeology of Mining and Field Survey •• Ethnoarchaeology •• Chemical Analysis and Provenance Studies •• Conservation Studies  With chapters focused on most geographic regions of Archaeometallurgical inquiry, researchers will find practical applications for metallurgical techniques in any area of their study.  Ben Roberts is a specialist in the early metallurgy and later prehistoric archaeology of Europe. He was the Curator of the European Copper and Bronze Age collections at the British Museum between 2007 and 2012 and is now a Lecturer in Prehistoric Europe in the Department of Archaeology at the Durham University, UK.  Chris Thornton is a specialist in the ancient metallurgy of the Middle East, combining anthropological theory with archaeometrical analysis to understand the development and diffusion of metallurgical technologies throughout Eurasia. He is currently a Consulting Scholar of the University of Pennsylvania Museum, where he received his PhD in 2009, and the Lead Program Officer of research grants at the National Geographic Society.